Strategi Belajar Pemagang Indonesia di Jepang dalam Meningkatkan Kemampuan Bahasa Jepang - Muryati, Sri; -, Trismanto; Astuti, Bekti Setio (KIRYOKU, 2024)
This study explores the strategies Indonesian interns employ to enhance their Japanese language proficiency during internships in Japan. A qualitative research method was utilized, collecting data through an online survey from 90 respondents. The survey included information on personal characteristics, learning strategies, experiences, and challenges encountered during the learning process. Analysis revealed that most interns were male (86.7%) with a predominant age range of 26-30 years, most of whom had resided in Japan for over 2 years. While many had educational backgrounds equivalent to high school, their initial proficiency levels in Japanese varied, with most starting at level N4. Common learning strategies included self-study using media such as videos (including films and TV shows), reading Japanese textbooks, and practicing speaking with friends. Direct interaction with native Japanese speakers outside work contexts was also considered crucial. Despite relatively low participation in formal Japanese language classes, respondents found their chosen self-study methods to be effective. Primary challenges included time constraints and difficulties in grasping Japanese grammar. Effective strategies identified for improving Japanese language proficiency among interns encompass consistent self-directed learning, direct interaction with native speakers, and the use of relevant learning resources. The implications of this research underscore the importance of adapting to irregular work schedules and maintaining high motivation to achieve significant progress in mastering the Japanese language.